'Emptiness Makes Water Flow Uphill': Eckhart, Justice, and Mercy in the Dominican Tradition. Issue 2 (2nd July 2016) - Pierce O.P., Brian J.
Abstract : Meister Eckhart, the 13th Century Dominican preacher and mystic, was a master of paradox. Clearly one of the great mystical theologians of the Ground, Eckhart's teaching and preaching style was less focused on communicating theological information and truths and much more concerned with provoking in his listeners an encounter with God. That encounter, in typical Eckhartian style, was meant to turn the listener's world upside-down, leaving him or her face-to-face with Truth. Using paradox in a way similar to a Buddhist master's use of a koan, Eckhart intentionally leads his disciple away from rational considerations into the mystery of the living God. This essay, weaving together threads from Eckhart's Book of Divine Comfort and the story of the man born blind in the Gospel of John (9:1–41), intends to lead us into a discovery of our own inner river of divine life.